Virulence of Icelandic Pyrenophora teres f. teres populations and resistance of Icelandic spring barley lines - Novakazi, Fluturë; Göransson, Magnus; Stefánsson, Tryggvi Sturla; Hokka, Marjo; Jalli, Marja; Hallsson, Jón Hallsteinn (Journal of Plant Pathology, 2021)
Abstract The causal agent of the barley net blotch disease, Pyrenophora teres , is known for its high level of diversity due to sexual reproduction. Different pathotypes, defined by a virulence combination, even within the same fields are frequently found and virulence between locations can vary considerably. Evaluation of virulence patterns of a pathogen population is essential for breeding resistant cultivars suitable for specific locations. To identify virulence patterns in Icelandic Pyrenophora teres f. teres (Ptt) isolates, twenty single spore isolates of Ptt were collected from seven locations in Iceland and analysed with AFLP markers. Principle Coordinate Analysis (PCoA) revealed Icelandic Ptt isolates clustering away from reference isolates from Austria, Finland, Sweden, Switzerland, UK, and USA. Hierarchical clustering grouped the Icelandic isolates into three distinct groups. Furthermore, the virulence of these twenty isolates was tested on 16 barley differential lines and revealed high variation in their virulence. Twenty-one barley cultivars commonly used in Iceland showed high susceptibility towards inoculation with Icelandic Ptt isolates.